2019
DOI: 10.14358/pers.85.10.737
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Detection of Built-Up Areas from High-Resolution Remote Sensing Imagery Using a Fully Convolutional Network

Abstract: The analysis of built-up areas has always been a popular research topic for remote sensing applications. However, automatic extraction of built-up areas from a wide range of regions remains challenging. In this article, a fully convolutional network (FCN)–based strategy is proposed to address built-up area extraction. The proposed algorithm can be divided into two main steps. First, divide the remote sensing image into blocks and extract their deep features by a lightweight multi-branch convolutional neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It also has higher processing efficiency for the detection of built-up areas in a wide range of images. Recent research has shown that block-based CNN models have significant advantages over traditional hand-crafted feature methods [37], [38], [39]. However, the existing block-based supervised detection still needs to address the following issues.…”
Section: Introductionmentioning
confidence: 99%
“…It also has higher processing efficiency for the detection of built-up areas in a wide range of images. Recent research has shown that block-based CNN models have significant advantages over traditional hand-crafted feature methods [37], [38], [39]. However, the existing block-based supervised detection still needs to address the following issues.…”
Section: Introductionmentioning
confidence: 99%
“…A supervised DL model [10], [92], [98], [119] generally requires a massive number of labeled images input for training. Although the CNN model [83], [118] that relied on supervised learning has greatly improved the LUM performance of HSR-RSI. An unsupervised learning approach [120]- [122] that utilizes small amounts of images with no labels is still aroused attention continuously as labeled training samples are not largely available until now.…”
Section: Summary Of Dl-based Lum Methodsmentioning
confidence: 99%
“…So obviously, this kind of approach does not apply the whole image as input, which leads to redundant processing and decrease efficiency when predicting labels of large scale HSR-RSIs. The second segmentation method is based on pixel-to-pixel and end-to-end [33], [98], [118], [156]. It can directly infer pixel-based labels of the whole patch or image.…”
Section: B Pixel-based or Object-basedmentioning
confidence: 99%
“…However, due to the effect of image segmentation quality, expressing HR complex scenes is difficult for image objects. Recently, block-based deep learning methods have been applied to extract built-up areas from HR images [12,[35][36][37]. An image block typically contains multiple objects and their spatial distribution patterns.…”
Section: Introductionmentioning
confidence: 99%